EDUKASI MP-ASI CEGAH STUNTING DENGAN METODE EMO-DEMO CEMILAN SEMBARANGAN DI POSYANDU BALITA - Tati Nuryati; Handayani, Handayani; Elyin Artha Karlina (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Based on the results of Basic Health Research (Riskesdas) in 2013 the prevalence of stunting under five (height per age) in Indonesia reached 37.2%, while the World Health Organization (WHO) limit was less than 20% (Ministry of Health RI, 2017)(Dewina, 2021) . Whereas in Panangkatan Village, Banjarharjo District, Brebes Regency, in 2021 there will be 636 toddlers with stunting cases, 105 toddlers (16.6%) below the national figure, while in 2021 the number of toddlers is 655 toddlers with stunting cases 73 toddlers, (11.1%) ) malnutrition 14 toddlers, malnutrition 56 toddlers (Nuryati & Hanna, 2022). Based on the preliminary survey, most mothers who have children under two years old in Panangkatan Village, Banjarharjo District, Brebes Regency, provide unhealthy snacks as complementary food to breast milk (MP-ASI). Meanwhile, when they come to Posyandu every month they get additional food in the form of eggs, bananas, sometimes peanut porridge, etc. To change the behavior of mothers under five regarding MP-ASI, they have never been given counseling on healthy snacks to accompany ASI with the EMO-DEMO method. The problem of stunting, one of the disorders of malnutrition in toddlers, is still a concern of the government. Thus the LPPM UHAMKA Partner Cooperation Program (PKM) in community service offers a solution for MP-ASI Education to Prevent Stunting with the EMO_DEMO Method of Random Snacks at Posyandu Mawar 2 Panangkatan Village, Banjarharjo District, Brebes Regency. The purpose of this community service is to increase the knowledge, attitudes and behavior of mothers under five in providing complementary foods for breastfeeding. The MP-ASI education method that will be carried out with EMO-DEMO with the following stages: Coordinating with the head of Panangkatan Village, Dera Asyifa Hospital Banjarharjo, and the Bandungsari Health Center, identifying the nutritional status of toddlers, counseling on the impact of stunting on toddler health and the CONTENTS OF PIRINGKU, MP-ASI Education process using the EMO-DEMO method of random snacks, evaluating and recording reporting. The results of community service through the pretest and posttest, it turns out that the results show that there is a difference between the respondent's knowledge score before education with a score of 66 and after being given education with a score of 80.3. Apart from going through the pretest posttest also by asking questions about the material that has been presented, where participants who can answer get prizes from the committee, and it turns out that almost all participants can answer all the quiz questions with prizes